Caracterização e aptidão agrícola de solos representativos do agropólo mossoró-assu - Silva, Álisson Gomes da (2018)
For understanding the most appropriate management, it is necessary to reseach the types of soil that a region has. In this way, constant appraisement of soil attributes is necessary so that the various agricultural uses are analyzed and established in the most appropriate way. The state of Rio Grande do Norte has one of the largest productions of fruits, vegetables and grains of the northeast region, part of this production is located in the Agropólo Mossoró-Assu, inserted in the region of the state of Rio Grande do Norte, where the most prevailing soils are occurs such as Cambissolo (Inceptisol), Neossolo (Entisol) and Latossolo (Oxisol). The aim of this work was to characterize the representative soils of the Agropólo Mossoró-Assu region and to define the agricultural aptitude of such areas, as well as to understand the genesis of the soils that represent the area. Morphological, physical, chemical and mineralogical analyzes of the representative profiles that compose Agropólo Mossoró-Assu were carried out. The studied profiles were classified in four kinds of soils: Latossolo (Oxisol), Cambissolo (Inceptisol), Neossolo (Entisol) and Chernossolo (Molisol). When observing the morphological attributes, it was noticed that there was great influence of principle material, for the distinction of the main kinds of soil that were found factor of origin in the distinction of the main kinds of soil found. The textural classification of the evaluated soils ranged from sandy to clayey, also influenced by the source material and the different processes of soil formation. Most of the soil profiles showed high base saturation, but only the Oxisol profile showed low base saturation in all its horizons, due to the intense weathering process, making the soil chemically poor. In relation to the iron oxide content of the soil, most of the profiles were classified as hypoferric, only the Inceptisol (profile 3) presented a meso-ferric character, the profile of Oxisol presented the highest amount of crystalline iron and the smaller amount of amorphous iron, since in the profiles of Entisol the amounts of amorphous iron are close to the crystalline, showing even more that the process of weathering is the factor that directly interferes with the amount of iron oxides. The mineralogy showed evident peaks of kaolinite and ilite, as well as hematite and goethite, indicative of more weathered soils with a reddish coloration, and peaks of minerals of type 2:1 in P3 and P5, evidencing very weathered soils. The classification of agricultural land aptitude was made, showing that the majority of the evaluated profiles showed up a aptitude, where the main limiting factor evidenced among them was water